Hair Cortisol: A Biomarker of Chronic Stress in Animals and its Association with Reproduction - Gupta, Akanksha; Yadav, Usha; Bansal, Krishna N; Bishnoi, Manju Bala; Bala, Renu; Verma, Nisha; Bhardwaj, Shivani; Kumar, Pradeep; Kumar, Dharmendra; Yadav, P S (Animal Reproduction Update, 2023)
Hair cortisol concentration (HCC) is used to assess the long-term retrospective measurement of the hypothalamic-pituitary-adrenal axis (HPA axis). HCC reflects HPA axis activity over a period of months and years depending on hair growth rate and length of hair measured. HCC is being used as a biomarker of chronic stress in order to check the well-being of domestic animals (cattle, horses, dogs, pigs), wild animals, captive animals, human trauma victims, and post-traumatic stress disorders (PTSD) as it provides an innovative approach to measure chronic HPA activity retrospectively over months without being affected by short term acute stressors and diurnal patterns. Stress plays a significant role in affecting the fertility of animals. Activation of the HPA axis further activates the hypothalamic–pituitary–gonadal axis (HPG) i.e., glucocorticoids are produced causing apoptosis of Leydig cells and decreased testosterone levels in males. In females, increased cortisol levels can suppress the tonic secretion of Leutinizing hormone (LH) which might hamper ovulation. Thus, hair cortisol analysis for assessment of the HPA-HPG axis could be a very important tool for animal welfare.
Keywords: Key words: Stress, Hair cortisol, HPA axis, HPG axis, animal welfare